Incidence, Clinical Features, and Outcomes of the Confirmed Neonatal COVID-19 Infection in the Southwest Iran - Najmeh Maharlouei; Arash Khojasteh Zonoozi; Zaynab Noeizad; Atila Erami; Hamidreza Parsa; Zahra Eskandari Kootahi; Sara Raji; Kamran B. Lankarani (International Journal of Pediatrics)
Background. The impact of COVID-19 on the neonatal population is still mysterious. This study is aimed at reporting the prevalence of COVID-19 and its clinical characteristics and outcomes among neonates in Iran. Methods. We conducted a retrospective cohort including 25 neonates who had COVID-19 infection confirmed by reverse transcription polymerase chain reaction (RT-PCR). Based on neonates’ hospitalization records, data regarding neonatal and maternal characteristics and clinical and paraclinical findings were extracted. Results. In Fars Province, the incidence of COVID-19 among neonates was 47.5 per 100000 living births in one year. From 25 neonates, 20 cases (80%) were recovered, while five cases (20%) died, and all of them were symptomatic. Nine cases (37.5%) were preterm, and two cases (22.2%) belonged to deceased neonates. Four out of five deceased neonates (80%) suffered from congenital abnormalities, and all required respiratory support in the course of their disease progression. Also, 18 neonates (72%) were admitted to NICU. Moreover, the COVID-19 RT-PCR test of nine mothers (43.7%) became positive. Conclusions. This study showed that the incidence of confirmed and symptomatic SARS-CoV-2 infection among neonates in the Fars Province of Iran over one year was 47.5 per 100000 living births. Thoroughly evaluating the epidemiological factors associated with COVID-19, such as underlying health conditions and family history of COVID-19, is crucial in properly managing neonates during the pandemic and increasing awareness.